Pengaruh Krom pada Sambungan Las Terhadap Sifat Mekanik Baja Karbon dengan Elektroda E 6013 - Syaripuddin; Setyo Firman Alamsyah; Ferry Budhi Susetyo (Jurnal Asiimetrik: Jurnal Ilmiah Rekayasa Dan Inovasi, 2021)
This study aims to determine the effect of the addition of chromium in the SMAW process to the tensile strength, hardness value and macro structure of the low carbon steel welding joint using E6013 electrodes. The research procedure begins with the process of welding, making seam, making specimens: tensile test, hardness test and macro structure. Furthermore, the process of tensile, hardness and macro structure testing is carried out. The tensile strength value of the weld joint with the addition of chrome tends to be slightly smaller than that of the weld without the addition of chrome. The maximum tensile stress and elasticity limits for welded joints with added chrome are higher than for welded joints without added chrome. The addition of chrome to the welding process has been shown to increase hardness. In the macro structure, porosity did not occur both specimens with the addition of chromium and without the addition of chromium.